Automated Analysis of Voting Systems with Dolev-Yao Intruder Model - Moran, Murat; Heather, James (Electronic Communications of the EASST, 2014)
This paper presents a novel intruder model for automated reasoning about anonymity properties of voting systems. We adapt the lazy spy for this purpose, as it avoids the eagerness of pre-computation of unnecessary deductions, reducing the required state space for the analysis. This powerful intruder behaves as a Dolev-Yao intruder, which not only observes a protocol run, but also interacts with the protocol participants, overhears communication channels, intercepts and spoofs any messages that he has learned or generated from any prior knowledge. We make several important modifications in relation to existing channel types and the deductive system. For the former, we define various channel types for different threat models. For the latter, we construct a large deductive system over the space of messages transmitted in the voting system model. The model represents the first formal treatment of the vVote system, which is planned for use in 2014 in state elections in Victoria, Australia.